2011
DOI: 10.1016/j.polymdegradstab.2011.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Stability of a salicylate-based poly(anhydride-ester) to electron beam and gamma radiation

Abstract: The effect of electron beam and gamma radiation on the physicochemical properties of a salicylate-based poly(anhydride-ester) was studied by exposing polymers to 0 (control), 25 and 50 kGy. After radiation exposure, salicylic acid release in vitro was monitored to assess any changes in drug release profiles. Molecular weight, glass transition temperature and decomposition temperature were evaluated for polymer chain scission and/or crosslinking as well as changes in thermal properties. Proton nuclear magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…37 H&E staining showed that with the extension of the implantation time in vivo, the bers of the scaffolds gradually degrade, and the degradation products of SF/PLCL scaffolds are amino acids from SF, and lactic acid and caproic acid from PLCL, and these are metabolizable and nontoxic. 38 Thus, these ndings indicate that SF/PLCL scaffolds could promote conjunctiva formation.…”
Section: Discussionmentioning
confidence: 75%
“…37 H&E staining showed that with the extension of the implantation time in vivo, the bers of the scaffolds gradually degrade, and the degradation products of SF/PLCL scaffolds are amino acids from SF, and lactic acid and caproic acid from PLCL, and these are metabolizable and nontoxic. 38 Thus, these ndings indicate that SF/PLCL scaffolds could promote conjunctiva formation.…”
Section: Discussionmentioning
confidence: 75%
“…Electron beam and gamma irradiation were chosen as other common sterilizing methods involve heat and/or moisture (e.g., dry heat, autoclaving, and ethylene oxide), which cause polyanhydride degradation. [15] Polymer samples were subjected to 0, 25, or 50 kGy doses (untreated, standard sterilizing dose, and maximum sterilizing dose, respectively) of either electron beam or gamma radiation. The irradiated polymers were then analyzed for changes in molecular weight or degradation rates.…”
Section: Resultsmentioning
confidence: 99%
“…Degradation media (1 mL) was removed and replaced by 1 mL PBS every 24 h for the first 7 days, then once more every 7 days until the experiment was finished. The spent media was analyzed by UV ( λ = 303 nm) with a Lamda XLS UV/vis spectrophotometer (Perkin Elmer, Waltham, MA) to determine the SA release as previously described . A calibration curve was made from SA solutions of known concentration from the average UV data ( n = 3 for each time point).…”
Section: Methodsmentioning
confidence: 99%